Perlakuan ikan zebra, Danio rerio di bawah aruhan tekanan bunyi, pemangsa dan persekitaran baru - Shazrul Fazry,; Amirulhakim Azizan,; Zahratul Nabila Dawa,; Nur Fitrah Abd Ghani,; Noor Fara Fatehah Roselan,; Muhammad Akram Mohd Noordin,; Malina Kumaran,; Herryawan Ryadi Eziwar Dyari,; Azwan Mat Lazim,; Luqman Abdul Aziz,; Babul Airianah Othman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this study, we observed the effect of sound, predatory and new enviroment on zebrafish behavior to determine which factor gives the most effect on the fish. Elevation of stress was observed on fishes that were moved consecutively into a container. Interestingly, this does not impair the fish feeding activity, even with the presence of a predator. Transfering of fish into different size of container also did not change the level of stress and anxiety in the fish. Zebrafish were also shown to have high cognitive ability to adapt to new sound condition in the enviroment, prefering constant and slow tempo compared to fast and erratic tempo. In conclusion, external environment such as sound and transfering of fish were able to effect fish behavior.